Diversity patterns and compositional variation of understorey plants in tropical forest of Mt. Pohen, Batukahu Nature Reserve, Bali - Mukaromah, Laily (Proceeding International Conference on Global Resource Conservation, 2015)
An understanding of the patterns in biodiversity is fundamentally important for efficient management of nature reserves. The objectives of this study were to: 1) investigate the diversity of understory plants in the tropical forest of Mt Pohen, Batukahu Nature Reserve, Bali, 2) explore patterns of understory plants in relation to underlying environmental factors. Field data collection was conducted to sample vegetation characteristics and the environmental parameters in the 78 quadrats of the study sites.Diversity indices (richness, diversity, and evenness) were measured and compared for each site. Environmental variables were plotted on the diagram produced by the NMDS to evaluate their relationship with the floristic patterns encountered. A total of 122 plant species were enumerated from 78 quadrats in the study area. Results show that Asteraceae and Poaceae were the predominant families in this study, followed by other most important families, i.e. Myrtaceae, Fabaceae, Moraceae, and Malvaceae. NMDS demonstrated the environmental variables most highly correlated with plant species distribution among the sites were altitude, humidity, light intensity, slope aspect and air temperature. Results also highlighted that fire and human disturbance likely play a significant role affecting biodiversity and vegetation characteristics in this forest ecosystem.Keywords: Batukahu Nature Reserve; environmental correlates; tropical forest; understorey